2004
DOI: 10.1016/j.brainresrev.2004.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Role of connexin-based gap junction channels and hemichannels in ischemia-induced cell death in nervous tissue

Abstract: Gap junction channels and hemichannels formed of connexin subunits are found in most cell types in vertebrates. Gap junctions connect cells via channels not open to the extracellular space and permit the passage of ions and molecules of ~1 kDa. Single connexin hemichannels, which are connexin hexamers, are present in the surface membrane before docking with a hemichannel in an apposed membrane. Because of their high conductance and permeability in cell-cell channels, it had been thought that connexin hemichann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
187
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 220 publications
(194 citation statements)
references
References 160 publications
(238 reference statements)
5
187
1
1
Order By: Relevance
“…Further, glutamate may leave the astrocytes through hemichannels, which can be opened by lowering of extracellular Ca 2 þ and acidosis or even through P2X 7 receptors, activated by excessively high extracellular ATP; all these do happen during ischaemia. 24 Second, astrocytes may spread the death signals through the brain parenchyma via gap junctions 25 and/ or participate in developing spreading depression, which determine the infarction progress through the penumbra.…”
Section: Glia and Neuropathology: General Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, glutamate may leave the astrocytes through hemichannels, which can be opened by lowering of extracellular Ca 2 þ and acidosis or even through P2X 7 receptors, activated by excessively high extracellular ATP; all these do happen during ischaemia. 24 Second, astrocytes may spread the death signals through the brain parenchyma via gap junctions 25 and/ or participate in developing spreading depression, which determine the infarction progress through the penumbra.…”
Section: Glia and Neuropathology: General Perspectivesmentioning
confidence: 99%
“…Indeed, it has been recently reported that Cx hemichannels, which are normally closed became open under experimental ischaemia induced by glucose and oxygen deprivation. 24 Up-to-now, a number of factors may account for the above apparent contradictions. 44 For instance, experimental studies vary considerably with regard to the systems employed and the way used to block hemi-or full-Cx channel-mediated communication.…”
Section: Intercellular Communication In Glia and Neuroprotectionmentioning
confidence: 99%
“…The gap junction "bystander effect" occurs when a dying cell delivers a cellular apoptotic signal such as high Ca +2 or ATP to an adjacent cell through open gap junctions which, in turn, causes spread of the death signal [4]. The process is well-documented in brain ischemia [10][11][12]. Retinal ischemia induces retinal cell death in a caspase-dependent manner [13].…”
Section: Introductionmentioning
confidence: 99%
“…During ischemia or stroke, cell death signals may pass through gap junction channels to adjacent cells (Velaquez et al, 2003;Contreras et al, 2004;Thompson et al, 2006). This gap junction "Bystander effect" accounts for cell death (Farahani et al, 2005).…”
Section: Discussionmentioning
confidence: 99%